Current Understanding of Temperature Stress-Responsive Chloroplast FtsH Metalloproteases - Shengji Luo (MDPI AG, 2021)
Low and high temperatures are life-threatening stress factors, diminishing plant productivity. One of the earliest responses of plants to stress is a rapid burst of reactive oxygen species (ROS) in chloroplasts. Widespread efforts over the past decade shed new light on the chloroplast as an environmental sensor, translating the environmental fluctuation into varying physiological responses by utilizing distinct retrograde (chloroplast-to-nucleus) signals. Recent studies have unveiled that chloroplasts mediate a similar unfolded/misfolded/damaged protein response (cpUPR) as observed in the endoplasmic reticulum and mitochondria. Although observing cpUPR is not surprising since the chloroplast is a prime organelle producing harmful ROS, the intertwined relationship among ROS, protein damage, and chloroplast protein quality controls (cpPQCs) with retrograde signaling has recently been reported. This finding also gives rise to critical attention on chloroplast proteins involved in cpPQCs, ROS detoxifiers, transcription/translation, import of precursor proteins, and assembly/maturation, the deficiency of which compromises chloroplast protein homeostasis (proteostasis). Any perturbation in the protein may require readjustment of proteostasis by transmitting retrograde signal(s) to the nucleus, whose genome encodes most of the chloroplast proteins involved in proteostasis. This review focuses on recent findings on cpUPR and chloroplast-targeted FILAMENTOUS TEMPERATURE-SENSITIVE H proteases involved in cpPQC and retrograde signaling and their impacts on plant responses to temperature stress.